Thermal requirements to obtain calcined and frits of ulexite - Flores, Horacio Ricardo (2007)
Ulexite has a substantial amount of hydration water, which allows using calcination methods to increase the B2O3 content from 42.97 to 66.69%, due to the loss of 35.54% of its weight, corresponding to its hydration water. In this study, determinations of changes in the heat content at each temperature were made using an isoperibol calorimeter. The mean specific heat was calculated from these values. The reaction enthalpy was also determined by DTA methods. The sample used in the experiments contains 39.04% B2O3. The temperature was between 80 and 1000 °C. Curves of weight loss and enthalpy changes are presented and analysed. The results have industrial application in order to determine the thermal requirements for calcining ulexite at different temperatures, as well as its complete dehydration. © 2006 Elsevier B.V. All rights reserved.